Gambaran Kerasionalan Resep Antibiotik Dengan Diagnosa ISPA Di Poli Anak Rumah Sakit Prikasih Jakarta Selatan Periode Januari – Maret 2020 - Neneng Sri Purwanigsih; Dimas Agung Wijanarko; Ana Yuli Handayani (STIKes Kharisma Persada, 2021)
Irrational drug use is a major problem in the world. Irrational prescribing of drugs can be described as medically inaccurate and ineffective in financing, treatment There are many studies that describe the treatment of ARD (Acute Respiratory Disease) patients who tend to use antibiotics which lead to overprescription and become irrational. This research was to descripte of a rational antibacterial prescription with a diagnosis of upper Acute Respiratory Tract Infection (ARI) at Prikasih Hospital Children's Clinic. Methods for this research is descriptive method using retrospective data. Samples in this study were 380 recipes. The results showed that there were 79.7% rational recipes and 20.3% irrational recipes. Based on the choice of drug type, cefixime is the most widely used antibiotic with a rule of 3 times a day.